Application Level Scalable Leader Selection Algorithm for Distributed Systems - Sayyed, Zahir (International Journal of Computational and Experimental Science and Engineering, 2025)
Leader selection is a critical issue in distributed systems where a single node is elected from a number of nodes to perform specific tasks or to provide system consistency. This article proposes the design and implementation of a scalable leader selection algorithm that ensures efficiency in large-scale distributed environments. This algorithm is designed to minimize communication overhead, tolerate node failures and scale with the size of the system. Leader selection is the most important issue for distributed systems since it guarantees the coordination and efficiency of the system. In this paper, we propose a scalable leader selection algorithm that can adapt to the system size and network condition changes. We will discuss its design, implementation challenges and performance..